Cognitive Development of Children through Illustrated Letter Card Media in Kindergarten - Sukarti, Sukarti; Hidayati, Sri; Aghnaita, Aghnaita; Muzakki, Muzakki; Karim, Abdullah (Universitas Islam negeri Mahmud Yunus Batusangkar, 2023)
The early development of cognitive abilities is crucial due to its significant impact on a child's overall growth. This research aims to describe the cognitive development of children using picture letter cards at RA Mawaddah Palangka Raya. A qualitative method with a descriptive approach was employed, involving 1 teacher from group B, 15 children, and the Head of School at Mawaddah Palangka Raya as informants. Data were gathered through observation, interviews, and documentation, employing triangulation of techniques and sources. Analysis was conducted through data collection, reduction, presentation, and conclusion drawing. The research results indicate that out of 15 children, 2 are in the Early Development stage (ED), 6 are Developing as Expected (DE), and 7 are Developing Very Well (DVW). These achievements encompass the children's ability to organize and match picture letter cards, solve simple problems, and show initiative in choosing game themes. Additionally, the children demonstrated a good understanding of colors, shapes, and object sizes, recognized letters ABCD, and comprehended various vowel and consonant variations